Quaternion Based Fuzzy Neural Network Classifier for MPIK Dataset's View-invariant Color Face Image Recognition - Wong, Wai Kit; Lee, Gin Chong; Loo, Chu Kiong; Lock, Raymond (Informatica)
Quaternion Based Fuzzy Neural Network Classifier for MPIK Dataset's View-invariant Color Face Image Recognition